A Flurry of Blessings. (1st September 2016) - Zijian, Chi; Goodman, Eleanor
Abstract : Chi Zijian paints a kindhearted tale of a tireless working-class couple whose steadfast love for one another provides them with a bountiful life and keeps them warm against the harsh winter backdrop of poverty and constant, back-breaking labor .